Genital ambiguity: a cytogenetic evaluation of gender - Lekha, K. S.; Bhagyam, V.; Varghese, P. D.; Manju, M. (International Journal of Research in Medical Sciences, 2021)
Background: Genital ambiguity is a complex genetic disorder of sexual differentiation into male or female. The purpose of the present study is to correlate the sex of rearing with the genetic sex and to find out the prevalence of chromosomal anomalies in patients with ambiguous genitalia. The findings can help in proper diagnosis, genetic counselling, and the reassignment of sex, if necessary. Methods: In this cross-sectional study, 22 patients from north Kerala, ranging in age from 17 days to 17 years, were included. All cases were subjected to the following: a detailed history, physical examination, evaluation of clinical data, and cytogenetic analysis. Based on the standard protocol, peripheral blood lymphocyte culture was done. Chromosomal analysis was carried out with the help of an automated karyotyping system after G-banding of chromosomes. Results: Out of the 22 patients with ambiguous genitalia, 12 patients were genetic females with karyotype 46, XX, and nine patients were genetic males with 46, XY karyotype. One was a rare variant of Klinefelter syndrome with karyotype 49, XXXXY. The most common diagnosis was congenital adrenal hyperplasia, followed by partial androgen insensitivity syndrome. Discrepancies between genetic sex and sex of rearing were noted in 27% of the cases. Conclusions: This study unfolds the variable etiology of ambiguous genitalia and emphasizes the importance of karyotyping in diagnosis, proper assignment of the sex, and appropriate management of patients with genital ambiguity.